2018
DOI: 10.5534/wjmh.180005
|View full text |Cite
|
Sign up to set email alerts
|

Dehydroepiandrosterone and Erectile Function: A Review

Abstract: To review the contemporary knowledge regarding the dehydroepiandrosterone and erectile function. Medline was reviewed for English-language journal articles spanning the time between January 1990 and December 2017, using the terms ‘erectile function’, ‘dehydroepiandrosterone’. We used original articles and review articles that found to be relevant to the purpose of this review. Criteria included all pertinent review articles, randomized controlled trials with tight methodological design, cohort studies and retr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 81 publications
0
4
0
1
Order By: Relevance
“…Sexual function may be impaired by uncomfortable symptoms, 34,41 by lesions in specific areas which make sexual activity difficult 34 or by disease activity, 28,34 as proinflammatory cytokines and systemic inflammation can both alter sex hormone levels and cause vascular dysfunction 42 . As occurs in the general population, ageing can also cause ED, 34 due to a decline in dehydroepiandrosterone levels and atherosclerosis 43 . Some cultural factors may also be involved in SD, such as educational status, which may be explained by different lifestyles and expectations between people with different levels of education 34 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sexual function may be impaired by uncomfortable symptoms, 34,41 by lesions in specific areas which make sexual activity difficult 34 or by disease activity, 28,34 as proinflammatory cytokines and systemic inflammation can both alter sex hormone levels and cause vascular dysfunction 42 . As occurs in the general population, ageing can also cause ED, 34 due to a decline in dehydroepiandrosterone levels and atherosclerosis 43 . Some cultural factors may also be involved in SD, such as educational status, which may be explained by different lifestyles and expectations between people with different levels of education 34 .…”
Section: Discussionmentioning
confidence: 99%
“…42 As occurs in the general population, ageing can also cause ED, 34 due to a decline in dehydroepiandrosterone levels and atherosclerosis. 43 Some cultural factors may also be involved in SD, such as educational status, which may be explained by different lifestyles and expectations between people with different levels of education. 34 Psychological factors may also play a role.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, adrenopause, which is caused by the decreased concentration of adrenal androgens, such as DHEA‐S, has gained increased attention, as has LOH 13 . An epidemiological study reported that DHEA‐S is relatively high in long‐lived groups, 14 because it has many physiological roles, and is deeply involved in reproductive and sexual functions, depression, cognitive function, obesity, and arteriosclerosis associated with metabolism and reducing bone density 12–18 . IGF‐1, which is produced primarily in the liver under the direct influence of growth hormone, is important not only in somatic growth, but also in metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…DHEA dapat digunakan untuk mengaktifkan saluran kalium melalui aktivasi guanylate cyclase yang larut dan meningkatkan fungsi endotel melalui peningkatan sintesis nitrit oksida (NO) untuk pelebaran arteri dan memblokir vasokonstriksi yang diinduksi hipoksia. Melalui mekanisme yang dipicu oleh membran plasma, DHEA secara akut meningkatkan pelepasan NO dari sel-sel endotel vaskular yang utuh (El-Sakka, 2018).…”
Section: Pendahuluanunclassified